2017
DOI: 10.18178/ijiet.2017.7.5.895
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of Collaborative Problem-Solving Strategies on Students’ Performance of Simulation-Based Learning — A Case of Network Basic Concepts Course

Abstract: Abstract-The continued development of the Internet has caused the concepts of network infrastructure and simple network troubleshooting to become important teaching objectives of certain college curricula. However, the abstract nature of network concepts and the high cost of equipment for network-related practice have become educational challenges for teachers in the relevant fields. Therefore, simulation learning and simulation learning software have become major instructional tools to assist teachers. Unfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In a heterogeneous group, one has different or limited ability and viewpoints, so group members should collaborate with one another and communicate and negotiate to agree on the most appropriate solution. Previous studies also indicated that collaborative problem solving can assist students to learn and promote their learning performance [2], [23]. Consequently, the present study follows the nine steps of collaborative problem solving to teach and use Facebook as a platform to investigate and record learners' learning outcome and process of discussion.…”
Section: B Collaborative Problem Solving (Cps)mentioning
confidence: 98%
“…In a heterogeneous group, one has different or limited ability and viewpoints, so group members should collaborate with one another and communicate and negotiate to agree on the most appropriate solution. Previous studies also indicated that collaborative problem solving can assist students to learn and promote their learning performance [2], [23]. Consequently, the present study follows the nine steps of collaborative problem solving to teach and use Facebook as a platform to investigate and record learners' learning outcome and process of discussion.…”
Section: B Collaborative Problem Solving (Cps)mentioning
confidence: 98%
“…Frezzo, Behrens and Mislevy (2010) also mentioned that using Packet Tracer could provide students with a learning environment with better a system logic. Besides, other researchers also stated that using Packet Tracer in teaching could promote students' learning interest and learning outcome [12]- [14].…”
Section:  Network Troubleshooting Examination Papermentioning
confidence: 99%
“…The positive results of this study are also in line with various previous studies which also examined the positive impact of CPS learning models implementation. Some of these studies reported that the application of CPS was able to increase student interest (Yin, 2015), learning outcomes (Lu & Lin, 2017) and students' academic achievement (Putra et al, 2018).…”
Section: Resultsmentioning
confidence: 99%